The effect of the incorporation of the flour of the worm of compost (Eisenia foetida) (Savigny, 1928) in the feed of tilapia Oreochromis niloticus high out in basin - HOUNDONOUGBO, Pierre; ADITE, ALPHONSE (My University, 2017)
The present study aims at determining the optimal and maximum quantity of the flour of worm of manure E. foetida in the feed of fingerlings of O niloticus. The experiment has been carried out of basins square of 1m ~ 6 ~ 3 of volume during 45 days from October at November 2016. During the period of acclimatization which lasted three days the fingerlings of initial average weight 4.79 ± 0.23 g have been nourished with Coppens. They have been then subjected to five treatments (T0; T5; T10; T15 and T20 corresponding to contents of 0%; 5%; 10%; 15% and 20% of flour of worm of manure in feed. At the end of the experiment the final average weights calculated was in the between 33.18 ± 13.71 g and 56.70 ± 14.65 g according to treatments'. Thus, the variance analysis with single direction (Anova1) with Statview 5.1 indicates that no significant difference exists between the various rates of survival. However, a significant difference between the various specific growth rates (from 3.45 ± 0.31%/day to 6.67 ± 0.30%/day) was observed. According to the mathematical model (amount-answer) based on the polynomial regression of the second degree, the maximum rate of incorporation of the flour of worm of manure in feed of fingerlings of O niloticus high out of basin under the conditions of this study was 13,82%.
Keywords: Content; worm of manure; maximum; Optimum; O. niloticus